Meningkatkan Fungsi Lobus Frontal melalui Permainan Labirin untuk Anak Usia 5-6 Tahun - Latifah, Reni; Suryani, Temi; Lingga, Doriska Vino (TSAQOFAH, 2024)
This study aims to develop a maze in the form of a game based on a valid and practical interactive media theme for children aged 5-6 years at jalan telaga dewa 10 kota bengkulu. The development of a maze game based on interactive media according to this theme uses a combination of the ADDIE development model and Tessmer's evaluation. The ADDIE development model consists of 5 stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. At the evaluation stage, a formative evaluation was carried out which was proposed by Tessmer consisting of four stages, namely the self-evaluation stage, expert review, one-to-one evaluation and small group evaluation. The data collection technique used observation. The results of the expert review obtained a recapitulation of the average value of the assessment results from material experts and for the media aspect of 3.80 (Very Valid Category) because the indicators and materials that are in accordance with mathematics learning for children aged 5-6 years are counting and logical thinking activities. The one to one evaluation stage obtained a recapitulation of the results of the analysis of children's observation data on the use of the Interactive Media-Based Maze Game of 89.5% (Very Good Category). The small group evaluation stage obtained a recapitulation of the results of the analysis of children's observation data on the use of Interactive Media-Based Maze Games of 92.56% (very good category). Interactive Media-Based Maze Games According to this Theme are declared valid and practical for use on children in the ongoing learning and teaching process.